2012
DOI: 10.1530/jme-11-0077
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and processing of secretogranin II in relation to the status of pheochromocytoma: implications for the production of the tumoral marker EM66

Abstract: We have previously demonstrated that measurement of tissue concentrations of the secretogranin II (SgII or SCG2 as listed in the HUGO database)-derived peptide EM66 may help to discriminate between benign and malignant pheochromocytomas and that EM66 represents a sensitive plasma marker of pheochromocytomas. Here, we investigated the gene expression and protein production of SgII in 13 normal adrenal glands, and 35 benign and 16 malignant pheochromocytomas with the goal to examine the molecular mechanisms lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…We additionally found that EM66 levels are significantly increased in the plasma of patients with pheochromocytomas [29]. We also demonstrated that low tissue concentrations of the peptide are associated with malignant differentiation of these neoplasms [30], [31]. Our data suggested that EM66 could potentially be a new diagnostic and prognostic marker of pheochromocytomas, and that, besides CgA, other granin-derived peptides, such as EM66, could represent valuable supplementary markers for the management and follow-up of these tumors.…”
Section: Introductionmentioning
confidence: 51%
“…We additionally found that EM66 levels are significantly increased in the plasma of patients with pheochromocytomas [29]. We also demonstrated that low tissue concentrations of the peptide are associated with malignant differentiation of these neoplasms [30], [31]. Our data suggested that EM66 could potentially be a new diagnostic and prognostic marker of pheochromocytomas, and that, besides CgA, other granin-derived peptides, such as EM66, could represent valuable supplementary markers for the management and follow-up of these tumors.…”
Section: Introductionmentioning
confidence: 51%
“…CgA is also used as a marker of tumour burden and relapse following treatment . Recently, EM66, a secretogranin II‐derived peptide, and neuron‐specific enolase (NSE) have been shown to be promising in distinguishing between benign and metastatic disease .…”
Section: Biochemical Tests For Confirming the Diagnosis And Their Rolmentioning
confidence: 99%
“…Although elevated levels of many granin-derived peptides are found in PCCs/PGLs, they rarely help to discriminate between benign and malignant tumors [80]. Recently, EM66, a secretogranin II-derived peptide present in chromaffin cells, has shown the most promise in early studies in distinguishing between benign and malignant disease [81,82]. Malignant disease demonstrated lower gene expression and protein transcription, but this has yet to translate into a measurable circulating biomarker.…”
Section: Biochemical Markers Of Malignancymentioning
confidence: 99%